Deletion of FUNDC2 and CMC4 on Chromosome Xq28 Is Sufficient to Cause Hypergonadotropic Hypogonadism in Men - Deng, Xinxian; Fang, He; Pathak, Asha; Zou, Angela M.; Neufeld-Kaiser, Whitney; Malouf, Emily A.; Failor, Richard A.; Hisama, Fuki M.; Liu, Yajuan J. (Frontiers in Genetics, 2020)
Background Hypergonadotropic hypogonadism (HH) is characterized by low sex steroid levels and secondarily elevated gonadotropin levels with either congenital or acquired etiology. Genetic factors leading to HH have yet to be fully elucidated. Methods Here, we report on genome and transcriptome data analyses from a male patient with HH and history of growth delay who has an inherited deletion of chromosome Xq28. Expression analyses were done for this patient and his unaffected family members and compared to normal controls to identify dysregulated genes due to this deletion. Results Our patient's Xq28 deletion is 44,806bp and contains only two genes FUNDC2 and CMC4. Expression of both FUNDC2 and CMC4 are completely abolished in the patient. Gene ontology analyses of differentially expressed genes in the patient in comparison to controls show that significantly up-regulated genes in the patient are enriched in Sertoli cell barrier regulation, apoptosis, inflammatory response and gonadotropin-releasing regulation. Indeed, our patient has an elevated FSH level, which regulates Sertoli cell proliferation and spermatogenesis. In his mother and sister, who are heterozygous for this deletion, X-chromosome inactivation is skewed towards the deleted X, suggesting a mechanism to avoid FSH dysregulation. Conclusion Compared to the previously reported men with variable sized Xq28 deletions, our study suggests that loss of function of FUNDC2 and CMC4 results in dysregulation of apoptosis, inflammation and FSH, and is sufficient to cause Xq28-associated HH.